Essentials of digital construction : lessons learned from digital transformation - Caballero, Amador (Emerald Publishing Limited, 2024)
Essentials of Digital Construction is an essential practical companion to facilitate the effective adoption of digital technologies in construction. It includes guidance on key issues that often arise, provides clarity based on real-life examples, and shows how to deploy digital technologies that are user-centric, scalable and cost-effective. With numerous case study examples, the book provides insights into key lessons that have been learnt on digital transformation. Topics covered include: business transformation and cultural change working effectively with the supply chain practical applications of data and artificial intelligence in construction how BIM and information management supports better project outcomes common issues that arise within projects and how to address them answers to frequently asked questions. Essentials of Digital Construction is a concise practical reference to help professionals and companies navigate the key issues and accelerate the process of implementing digital construction. It is an essential guide for contractors, design consultants, and subcontractors as well as digital specialists and anyone else involved in implementing digital construction.